The Use of Picture Media in Teaching German Vocabulary for Students’ at Senior High School I Tondano Minahasa - Denny R. Sarajar (AIBPM Publisher, 2020)
One of the teacher's strategies in overcoming students' lack of vocabulary mastery is by using Picture Media (Visualmedient). And this is what will be studied in this study by limiting the use of picture media to the vocabulary mastery of German students at Senior high school 1 Tondano in Minahasa. This study aims to obtain an overview of the benefits of picture media amid the increasingly digital modernization of science in the Millennial era and the impact of the success of learning German vocabulary. The research method used in this study is descriptive experiment and documentation. Based on the analysis obtained from the results of this study, it is proven that there is a positive influence on the use of picture media in teaching German vocabulary for students of senior high school 1 Tondano. Recognizing new vocabulary in German. This means that the pictures shown or displayed by the teacher will help accelerate students' recognition of German. After direct observation and demonstration of pictures, there is a significant difference between those who use pictures and those who do not use pictures as media. Students who learn vocabulary using pictures will have better results than students who do not use pictures. This is obtained through the final test of the lesson. The use of picture media in teaching German, in particular, learning vocabulary, has a very strong and positive effect on learning outcomes in German. Even though the digital millennial era is more dominant in using electronics, picture media is still needed in teaching German vocabulary. The vocabulary that is accompanied by pictures will make students remember the vocabulary because of the help of pictures.